Revitalisasi Perpustakaan Guna Meningkatkan Kualitas Literasi Baca Tulis Siswa MI Pembangunan Sidomukti Lamongan - Pratiwi Viyanti; Yulia Pramusinta; Yussi Puspita Anggraeni Faradilla (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The purpose of the library revitalization activity is to improve students' literacy and restore the function of the library. This service was carried out at MI Pembangunan Sidomukti Lamongan in Lamongan District, Lamongan Regency, and involved all students, facilitators, principals, and teachers of MI Pembangunan Sidomukti Lamongan. This service uses the Participatory Action Research (PAR) Method. The result of this service is an increase in students' interest in reading. This is shown by the increase in literacy from written works and the return of the library to its function.